Pengaruh Pemberian Ekstrak Rimpang Temulawak (Curcuma xanthorrhiza Roxb.) Terhadap Jumlah Eritrosit Mencit (Mus musculus L.) Jantan BALB/c yang Diinokulasi Plasmodium Berghei Anka - AZARINE NEIRA AVISHA; PRAWESTY DIAH UTAMI (Universitas Hang Tuah, 2018)
ABSTRACT Malaria is still one of the most important infectious diseases in tropical countries because it can cause severe anemia and death. Nowadays, the choice for treatment of malaria is increasingly limited due to drug resistance. Hence, require the invention of new compounds to overcome them. The objective of this research was to perceive the effect of curcuma (Curcuma xanthorrhiza Roxb.) rhizome extract to the amount of erythrocytes in male BALB/c mice (Mus musculus L.) inoculated by Plasmodium berghei ANKA. This research was conducted experimentally with post-test only control group design using five groups of mice. One group was left normal while the other four groups were inoculated with Plasmodium berghei ANKA. From the groups inoculated with Plasmodium berghei ANKA, one group was given aquades and three other groups treated with curcuma (Curcuma xanthorrhiza Roxb.) extract with dose of 150 mg/KgBB, 100 mg/KgBB and 50 mg/KgBB for four days. On the fifth day, a blood test is performed to determine the amount of erythrocytes. The results of this study indicate that the amount of erythrocytesin male BALB/c mice (Mus musculus L.) inoculated byPlasmodium berghei ANKA and given rhizomesextract (Curcuma xanthorrhizaRoxb.) at doses of 150 mg/KgBB and 50 mg/KgBB wereinsignificantly decreased. Whereas the amount of erythrocytesin male BALB/c mice (Mus musculus L.) inoculated byPlasmodium berghei ANKA and given rhizomesextract (Curcuma xanthorrhiza Roxb.) at doses of 100 mg/KgBB weresignificantly decreased